Malaysian Sign Language Mobile Learning Application : A recommendation app to communicate with hearing-impaired communities - Hanayanti Hafit; Chiam Wui Xiang; Munirah Mohd Yusof; Norfaradilla Wahid; Shahreen Kassim (Institute of Advanced Engineering and Science, 2019)
Malaysian Sign Language (MSL) is an important language that is used as the primary communication method for the deaf communities with the others. Currently, the MSL is poorly known by the Malaysians and the existing platform of learning the sign language is inefficient, not to mention the incomplete functionality of the existing mobile learning application in the market. Hence, the purpose of developing this application is aimed to increase the knowledge and recognition of the public towards the MSL and allows them to learn the sign language more effectively. One of the features in this application is sign detection, which could analyze the image captured by phone camera into sign meaning. The application also comprised various categories of the sign for efficient learning and quiz to test user knowledge against their learned sign language. Besides, there is a feedback module for the user to express their opinions and suggestions towards the application to the developer. This application is aimed to help the public to learn MSL efficiently by selecting the category of sign they wish to learn and test themselves by using the quiz module. Besides, the application could also detect the unknown sign by capturing the image and analyze it. The application helped to raise the recognition of MSL among the public and expose the public to the sign language knowledge. It had also become a small help in breaking the barrier of communication between the deaf communities and the public.